Cloud Based Gamification Model Canvas for School Information Management - Nordin A Rahman, M; Jaafar, Jazurainifariza; Fadzil A Kadir, M; Nor Shamsuddin, Syadiah; Iryani A Saany, Syarilla (International Journal of Engineering and Technology, 2018)
Information management especially related to teaching and learning materials is an important application in school in order to bring education system more effective and systematic. Modern education requires fundamental changes in current education system platform for ensuring teaching method becomes more efficient. The challenges of current school information management are non-integrated system, difficulty in configuration and deployment as well as complexity of storage provision. These issues reduce the motivation among teachers to participate in sharing teaching and learning materials in school information management system. This article proposes a gamification model canvas framework for school information management under cloud computing environment. The aim is to provide a method for encouraging the teachers to share their teaching materials. Motivation element provided in model canvas method such as dynamics, behavior, component and aesthetic are used in the proposed framework. With the proposed framework, a cloud based prototype will be developed and can be used by schools.Â